Sodium and nitrate favor the steady state of cyanobacteria in a semiarid ecosystem - Fábio Henrique Portella Corrêa de Oliveira (Acta Scientiarum. Biological Sciences, 2019)
This study characterized steady state events (SS) in a semiarid reservoir (Brazil) dominated by cyanobacteria for 130 weeks, and evaluated the influence of different abiotic variables on their occurrence. It was hypothesized that, in semiarid reservoirs, steady state events are independent from seasonality and influenced by high nutrient concentrations, and steady state periods show low variation of species. Our data revealed the occurrence of SS events in both the dry and wet seasons. Higher concentrations of nitrate and sodium together with higher values of color favored the development of SS. Species composing the SS dominated by Microcystis aeruginosa (Kützing) Kützing was correlated with higher sulfate concentrations, while higher values of turbidity and sodium concentrations favored the SS of Cylindrospermopsis raciborskii (Woloszynska) Seenaya and Suba Raju and Planktothrix agardhii (Gomont) Anagnostidis and Komárek. The results supported the hypothesis and showed the importance of variables rarely evaluated in works of this nature, such as sodium and sulfate in SS establishment of cyanobacteria.